Achieving Nearly 30% External Quantum Efficiency for Orange–Red Organic Light Emitting Diodes by Employing Thermally Activated Delayed Fluorescence Emitters Composed of 1, 8‐Naphthalimide‐Acridine Hybrids. Issue 5 (8th December 2017) - Zeng, Weixuan; Lai, Hsin‐Yu; Lee, Wei‐Kai; Jiao, Min; Shiu, Yi‐Jiun; Zhong, Cheng; Gong, Shaolong; Zhou, Tao; Xie, Guohua; Sarma, Monima; Wong, Ken‐Tsung; Wu, Chung‐Chih; et al.
Abstract: The combination of rigid acridine donor and 1, 8‐naphthalimide acceptor has afforded two orange–red emitters of NAI‐DMAC and NAI‐DPAC with high rigidity in molecular structure and strongly pretwisted charge transfer state. Endowed with high photoluminescence quantum yields (ΦPL ), distinct thermally activated delayed fluorescence (TADF) characteristics, and preferentially horizontal emitting dipole orientations, these emitters afford record‐high orange–red TADF organic light‐emitting diodes (OLEDs) with external quantum efficiencies of up to 21–29.2%, significantly surpassing all previously reported orange‐to‐red TADF OLEDs. Notably, the influence of microcavity effect is verified to support the record‐high efficiency. This finding relaxes the usually stringent material requirements for effective TADF emitters by comprising smaller radiative transition rates and less than ideal ΦPL s. Abstract : Orange–red organic light‐emitting diodes with external quantum efficiencies of up to 29.2% are achieved using excellent thermally activated delayed fluorescence (TADF) emission of 1, 8‐naphthalimide‐acridine hybrid. The relatively high photoluminescence quantum yield and horizontally oriented emitting dipoles of the TADF emitters combined with the influence of microcavity effects are verified to support the record‐high efficiency.